PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. RAJAWALI NUSANTARA INDONESIA (PERSERO) CABANG MEDAN - Silalahi, Gunawan; Sianturi, Marudut; Sinaga, Derlina (JURNAL PROINTEGRITA, 2020)
Performance can be influenced by many factors, including management, leadership, work ability, work discipline, training and work motivation. But the most important factors are the factors of leadership, work discipline and work ability. This study aims at finding the influence of leadership, work discipline, work ability partially and simultaneously on employee performance at PT. Rajawali Nusantara Indonesia (Persero) Medan Branch. The population of this research is 170 employees. To determine the number of samples, the Slovin formula is used and obtained as many as 63 people. Data collection techniques are such as questionnaires, interviews and documentation studies. While the data analysis techniques used are the classical assumption test, multiple regression, t test, F test and coefficient of determination. The results show that the significant influence of leadership on performance at PT. Rajawali Nusantara Indonesia (Persero) Medan Branch. When the leadership is better, the employee's performance is also better. The effect of work ability on performance is significant at PT. Rajawali Nusantara Indonesia (Persero) Medan Branch. It is found that better work discipline, performance is also better. The effect of significant work ability on performance at PT. Rajawali Nusantara Indonesia (Persero) Medan Branch is the better the work ability, the better the employee's performance.The variables of leadership, work discipline, work ability simultaneously have a significant effect on employee performance. It is recommended that company leaders need to give freedom to employees to make decisions in their respective fields of work, and avoid personal closeness with employees for matters that are not work-related. Leaders should only communicate with employees for matters related to office work. Company leaders need to improve employee attendance discipline and provide sanctions on the basis of the right considerations. Punishment should be imposed in proportion to the employee's error rate. Leaders need to place employees in work fields that are suitable for their educational backgrounds, and employees need to improve work experience, especially in the work field handled. Work experience can be improved by providing training in accordance with the work field of each employee.